Mitochondrial levels determine variability in cell death by modulating apoptotic gene expression - Silvia Márquez-Jurado (Nature Portfolio, 2018)
It is unclear what causes variation in cell death in response to chemotherapy. Here, the authors show that cellular mitochondrial content modulates apoptotic protein levels, which in turn regulates response to agents such as TRAIL.